Animals as sources of food-borne pathogens: A review - Heredia, Norma; García, Santos (Animal Nutrition, 2018)
Food-producing animals are the major reservoirs for many foodborne pathogens such as Campylobacter species, non-Typhi serotypes of Salmonella enterica, Shiga toxin-producing strains of Escherichia coli, and Listeria monocytogenes. The zoonotic potential of foodborne pathogens and their ability to produce toxins causing diseases or even death are sufficient to recognize the seriousness of the situation. This manuscript reviews the evidence that links animals as vehicles of the foodborne pathogens Salmonella, Campylobacter, Shiga toxigenic E. coli, and L. monocytogenes, their impact, and their current status. We conclude that these pathogenic bacteria will continue causing outbreaks and deaths throughout the world, because no effective interventions have eliminated them from animals and food.